Nūr al-dīn al-rānīrī’s concept of Islamic history in bustān al salāṭīn: A critical analysis of Book I-Book IV / Norhayati Hamzah - Norhayati, Hamzah (2017)
Nur al-Din al-Raniri was a renowned scholar of the 17th century Aceh in the era of Sultan Iskandar Thani (1636-1641 AD). His full name is Nur al-Din Muhammad bin ‘Ali bin Hasanji bin Muhammad Hamid al-Raniri al-Quraishi al-Shafi’i, originated from Ranir, Gujerat (henceforth Al-Raniri). Al-Raniri’s great contribution to the intellectual life in the Malay world has received considerable scholarly attention by scholars from the East and the West such as Van der Tuuk (1866), P. Voohoeve (1951), Braginsky (2004), Al-Attas (1966), Ahmad Daudy (1983) and Azyumardi Azra (2004). The majority of these scholars examine al-Raniri’s biography and his contribution to the Muslim society through his remarkable works on kalam and tasawwuf, but none of them truly concentrate on al-Raniri’s concept of Islamic history. Al-Raniri’s contribution to the field of history was no less profound. He was the first writer in the Malay-Indonesian World to initiate a new form of Malay historical writing and to introduce the concept of Islamic history in his historical work named Bustan al-Salatin fi Dhikr al-Awwalin wa al-Akhirin (The Garden of the Kings on the Recollection of the Past and Present/ The Garden of Kings, showing forth the origin of all creation and the end thereof) (cited hereafter Bustan). Bustan, consists of seven books with 60 chapters was written in Malay language using the Jawi writing. It is the best-known work of al-Raniri on history, which is a combination of a universal history and a “mirror for rulers” of the seventeen century Aceh. Therefore, this research endeavours to analyze al-Raniri’s concept of Islamic history in Bustan, from Book I-Book IV. It includes discussion on the purpose of writing, structure, contents, themes, sources and method of writing in Bustan. This research is a qualitative research that applies the techniques of documentation and interview in collecting data while inductive approach to content analysis was utilized for data analyzing. The main documents used were the three versions of the manuscript of Bustan (Raffles Malay 8, Raffles Malay 42 and UM 41). The outcome of this research reveals that the structure, contents, sources, and themes in Bustan are the reflection of al-Raniri’s concept of Islamic history.